Character Education in Indonesia Islamic Elementary Schools: A Systematic Literature Review (2014-2024) - Arif, Muhamad; Chapakiya, Suraiya; Dewi, Angela Yunda (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Educational institutions strive to shape students into individuals with character and noble morals, enabling them to integrate intelligence, intellectual, emotional, and spiritual aspects. Research on character education in elementary schools, specifically Madrasah Ibtidaiyah, presents diverse viewpoints. Based on the data above. The focus of this study is on three specific issues. The first issue is the pressing need for character education in both elementary schools and Islamic elementary schools, also known as madrasah ibtidaiyah. The second concern pertains to the various forms of character education students receive. The third issue pertains to the implementation of the character education model in Islamic elementary schools. The researchers employed the systematic literature review method. The articles were chosen based on five stages, and data analysis was done using PRISMA. The themes and time period covered the last ten years, from 2014 to 2024, and global data from Scopus and Google Scholar, which added up to 483 articles, book reviews, proceedings, and conferences. The study's results indicate that schools must effectively and efficiently implement character education in Islamic elementary school students, through coaching, mentoring, and individual approaches. In addition, schools must strengthen educational components such as curriculum, learning media, madrasah programs, and the government through the education office. while the types of characters implemented in Islamic elementary schools, include: religious character, nationalism, mutual cooperation, social, and discipline, which are supported by several character education models such as Thomas Lickona's character education model, the G-Gold Way model, participatory observation learning model, and an education model based on strengthening collaboration between schools and parents. The study's theoretical implications emphasize the importance of fostering a positive school culture as the primary solution.